Association Between Extraversion Personality With the Blood Pressure Level in Adolescents - Liang, Xiaohua; Hao, Guang; Xiao, Lun; Luo, Shunqing; Zhang, Guifang; Tang, Xian; Qu, Ping; Li, Rina (Frontiers in Cardiovascular Medicine, 2022)
Abstract 26 Purpose: The association between extraversion personality and high blood pressure (BP) has not been 27 well studied. This study aims to explore the association of extraversion personality and BP level in a 28 large sample of adolescents. 29 Methods: As an ongoing study, 5,246 children aged 6-9 years were recruited using a stratified cluster 30 sampling method in 2014. Extraversion personality trait, assessed by the Eysenck personality 31 questionnaire (EPQ, answered by adolescents) in 2019, was used in the main analysis. A total of 3,407 32 participants were eligible and included in this analysis. 33 Results: EPQ extraversion score was negative associated with systolic BP, diastolic BP, and mean arterial 34 pressure in univariate analysis. After adjusting for other covariates, a high extraversion score was 35 negatively associated with systolic BP (β=-0.026; 95%CI=-0.047, -0.004; P=0.002). There was an 36 interaction between region and extraversion score on the systolic BP (Pinteraction=0.037). Stratified 37 analysis showed that, in rural, the extraversion score was negative associated with systolic BP (β=-0.050; 38 95%CI=-0.081, -0.016; P=0.004). However, we did find an association between extraversion score and 39 systolic BP in urban (β=0.000; 95%CI=-0.028, 0.028; P=0.996). Similar results were observed for 40 extraversion assessed by parents. 41 Conclusions: We observed that extraversion personality was negatively associated with high BP in 42 adolescents, especially for living in the rural area. Our results suggested that comprehensive intervention 43 should be implemented to promote psychological health in adolescents.